Comparing the advantages, disadvantages and diagnostic power of different non-invasive pre-implantation genetic testing: A literature review - Noorodin Karami; Farzaneh Iravani; Sareh Bakhshandeh Bavarsad; Samira Asadollahi; Seyed Mehdi Hoseini; Fateme Montazeri; Seyed Mehdi Kalantar (Shahid Sadoughi University of Medical Sciences, 2024)
Abstract To improve embryo transfer success and increase the chances of live birth in assisted reproductive methods, there is a growing demand for the use of pre-implantation genetic testing (PGT). However, the invasive approaches used in PGT have led to in vitrofertilization failure and abortions, increasing anxiety levels for parents. To address this, non-invasive PGT methods have been introduced, such as the detection of DNA in blastocoel fluid of blastocysts and spent culture media (SCM). These methods have proven to be minimally invasive and effective in detecting aneuploidy in the chromosomes of human embryos. This review aims to explore the different approaches to pre-implantation diagnosis, including invasive and non-invasive methods, with a particular focus on non-invasive PGT (niPGT). The search strategy involved gathering data from scientific databases such as PubMed, Google Scholar, and Science Direct using relevant keywords. The search was conducted until January 2023. In total, 22 studies have successfully reported the detection and amplification of cell-free DNA in the embryonic SCM. It is important to note that niPGT has some limitations, which include differences in indicators such as cell-free DNA amplification rate, concordance, level of maternal DNA contamination, sensitivity, and specificity between SCM samples and biopsied cells. Therefore, more extensive and detailed research is needed to fully understand niPGT's potential for clinical applications.